Rehabilitation reference center (Ipswich, MA : EBSCO)
'Rehabilitation Reference Center is a clinical reference tool designed for use by rehabilitation clinicians, physical therapists, and occupational therapists at the point of care. It provides valid and relevant information intuitively and conveniently, using the best available evidence to help support clinical decisions.'--web site's Help page.
Mode of access : All issues available vie the World Wide Web
Keywords: Rehabilitation -- Databases; Occupational therapy -- Databases